WIT Transactions on the Built Environment 2011
DOI: 10.2495/str110381
|View full text |Cite
|
Sign up to set email alerts
|

Charts for the conservation of vernacular drystone retaining walls

Abstract: Drystone walls are durable structures, due to their intrinsic ductility, permeability, and the strength of the materials used. Nevertheless, they can be subject to slow deterioration due to the weathering of the materials, application of loads for which they were not designed, impact, or inappropriate repair methods. It is then necessary to assess the condition of the structure, and design repairs or a replacement construction. A suitable design should then help to minimize the overestimation of the structure'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Just over one third (35 %) of the population live in detached houses in EU (Eurostat, 2018). Le et al (2011) studied vernacular drystone retaining walls and showed that they can be subject to slow deterioration due to the weathering of the materials, application of loads for which they were not designed, impact, or inappropriate repair methods.…”
Section: Introductionmentioning
confidence: 99%
“…Just over one third (35 %) of the population live in detached houses in EU (Eurostat, 2018). Le et al (2011) studied vernacular drystone retaining walls and showed that they can be subject to slow deterioration due to the weathering of the materials, application of loads for which they were not designed, impact, or inappropriate repair methods.…”
Section: Introductionmentioning
confidence: 99%